TRANSLATION DIFFICULTIES IN TEACHING PROCESS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This artice focuses specifically on syntactic difficulties in translation, but issues in translation can manifest itself on different linguistic levels. In this section article summarises relevant literature in the field of (human) translatability.